The Strategy to Achieve Cost Leadership through Polymers Raw Material Cost Breakdown Analysis - Handayani, Widya; Rosita Asri, Nadya; Rabbani Yusuf, Achmad; Novali, Defri; Mutia, Andri (Adpebi International Journal of Multidisciplinary Sciences, 2025)
Purpose – This research explores the innovation strategy to achieve cost leadership through polymers raw material cost breakdown analysis at The OTO Company, a multinational manufacturing company. The goal is to identify, elaborate, implement, and evaluation the effectiveness of strategy to reach cost leadership in context of competitive advantage. Methodology/approach – Using qualitative methods, data were collected by interviews with the employees, direct observation and other secondary sources. Findings – The findings reveal that by implementing cost breakdown analysis and several supporting activities such as employee’s competencies upgrading and A-B-S monomers components brainstorming give the positive impact and support the purchasing function to strengthen their bargaining power and negotiation strategy, also impact to cost reduction or company budget saving. Novelty/value – The research suggests to do periodical checking of cost structure regarding environment or situation changing, also possibility for the conversion into automation to accelerate the cycle time of calculation.